2008
DOI: 10.1080/00365540801964960
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind study comparing Clostridium difficile immune whey and metronidazole for recurrent Clostridium difficile-associated diarrhoea: Efficacy and safety data of a prematurely interrupted trial

Abstract: A prospective, randomized, double-blind study was designed to compare Clostridium difficile immune whey (CDIW) with metronidazole for treatment of laboratory-confirmed, recurrent, mild to moderate episodes of Clostridium difficile-associated diarrhoea (CDAD). CDIW was manufactured by immunization of cows in their gestation period with inactivated C. difficile vaccine. The resulting colostrum was processed, immunoglubulins were concentrated and the end-product containing high titres of C. difficile immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 22 publications
0
54
0
Order By: Relevance
“…An oral anti-Clostridium whey protein from cows immunized to C. diffi cile toxoid was studied in the Netherlands. Early studies of C. diffi cile showed promise for treatment of patients with RCDI, with no further recurrences ( 128 ), but in a later study there was no signifi cant decrease in recurrences (44 % vs. 45 % ) ( 129 ). Further development of this product has been halted due to lack of funding.…”
Section: Other Investigational Treatmentsmentioning
confidence: 99%
“…An oral anti-Clostridium whey protein from cows immunized to C. diffi cile toxoid was studied in the Netherlands. Early studies of C. diffi cile showed promise for treatment of patients with RCDI, with no further recurrences ( 128 ), but in a later study there was no signifi cant decrease in recurrences (44 % vs. 45 % ) ( 129 ). Further development of this product has been halted due to lack of funding.…”
Section: Other Investigational Treatmentsmentioning
confidence: 99%
“…Oral administration of bovine anti-C. difficile IgA in whey protein purified from immunized cow's milk (Mucomilk) (MucoVax, BV., The Netherlands) has shown efficacy with a sustained response in human primary CDI treatment and recurrence reduction [Mattila et al 2008;van Dissel et al 2005]. However, studies were not continued to include larger patient cohorts.…”
Section: Localized Intraluminal Passive Immunotherapymentioning
confidence: 99%
“…None of the patients treated experienced recurrent CDI. In a later randomized, double-blind study, Mucomilk was found to be as effective as metronidazole in reducing recurrent CDI (Mattila et al, 2008). Unfortunately, this study was terminated early because of a lack of funding.…”
Section: The Need To Target Both Toxin a And B For Effective Immunothmentioning
confidence: 99%